Land law : text, cases, and materials - McFarlane, Ben; Hopkins, Nicholas, 1971-; Nield, Sarah (Oxford, United Kingdom : Oxford University Press, 2018)
Land Law: Text, Cases, and Materials offers a comprehensive, critical, and case-focused approach to the subject, combining insightful author commentary with carefully selected extracts to fully support students.
Part A: Introduction1: What's special about land?2: What is land?3: RegistrationPart B: The Content Question4: Human rights and land5: Legal estates and legal interests6: Equitable interests7: Personal rightsPart C: The Acquisition Question8: Formal methods of acquisition: contracts and deeds9: Informal methods of acquisition: adverse possession10: Proprietary estoppel11: TrustsPart D: The Shared Home12: Interests in the home: the acquisition question13: Regulating co-ownership: the content question14: Co-ownership and third parties: applications for salePart E: The Defences Question and Land Registration15: The priority triangle16: Registered land and priorities17: Overreaching18: The registered title, rectification and indemnityPart F: Leases19: Leases20: Regulating leases and protecting occupiers21: Leasehold covenantsPart G: Neighbours and Neighbourhoods22: Easements23: Freehold covenants24: Flat ownership: long leases and commonholdPart H: Security Interests25: Security interests in land26: Lender's rights and remedies27: Protection of borrower
Includes bibliographical references and index.
Keywords: Real property -- England -- Cases; Estates (Law) -- England -- Cases; Leases -- England -- Cases; Real property -- Wales -- Cases; Estates (Law) -- Wales -- Cases; Leases -- Wales -- Cases